2011
DOI: 10.1002/acp.1844
|View full text |Cite
|
Sign up to set email alerts
|

When Diversity in Training Improves Dyadic Problem Solving

Abstract: Students learned how to solve binomial probability problems from either a procedurally based lesson or a conceptually based lesson and then worked in distributed pairs by using a computer-based chat environment. Cognitively homogeneous dyads (i.e. both members received the same lesson) performed more accurately on standard problems, whereas cognitively diverse dyads (i.e. each member received a different lesson) performed more accurately on transfer problems. The cognitively homogeneous dyads perceived a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
(79 reference statements)
2
8
0
1
Order By: Relevance
“…A meta-analysis by Bowers et al (2000) concludes that while homogeneous teams tend to perform better on lowcomplexity tasks that are well-defined (e.g., solving a puzzle), heterogeneous teams perform better on rather complex problem-solving tasks (e.g., business games). Similar findings have been reported by Canham et al (2012): They asked university students to solve statistical probability problems either in homogeneous or in heterogeneous dyadic groups. Homo-/ heterogeneity of the dyads was varied as the type of training that group members received before collaboration.…”
Section: Reasoning About Authentic Problem Cases: Better Together?supporting
confidence: 84%
“…A meta-analysis by Bowers et al (2000) concludes that while homogeneous teams tend to perform better on lowcomplexity tasks that are well-defined (e.g., solving a puzzle), heterogeneous teams perform better on rather complex problem-solving tasks (e.g., business games). Similar findings have been reported by Canham et al (2012): They asked university students to solve statistical probability problems either in homogeneous or in heterogeneous dyadic groups. Homo-/ heterogeneity of the dyads was varied as the type of training that group members received before collaboration.…”
Section: Reasoning About Authentic Problem Cases: Better Together?supporting
confidence: 84%
“…This result converges with several other fi ndings in suggesting that diversity in expertise among group members can contribute to more adaptive, fl exible, and creative problem solving (Canham et al 2012 ;Gijlers and De Jong 2005 ;Goldenberg and Wiley 2011 ). Students who worked in mixed groups were better at explaining their understanding of standard deviation on a quiz following the activity than students who worked in homogeneous groups.…”
Section: Discussionsupporting
confidence: 89%
“…Gijlers and de Jong ( 2005 ) found that dyads engaging in discovery learning generated more hypotheses when they were heterogeneous in prior knowledge than when they were homogeneous. And Canham et al ( 2012 ) found that dyads were better at solving transfer items when their members were trained in different ways of solving probability problems than when both members had received the same training.…”
Section: The Present Studymentioning
confidence: 99%
“…This lack of interest can be exacerbated as many students are scared of statistics due to their lack of confidence in their mathematical ability (Ashcraft, 2002;Hembree, 1990). They also fail to understand that the goal of statistics instruction is not just to gain computational skills, but to understand concepts and to interpret results (Canham, Wiley, & Mayer, 2012;Mayer, 1974;Mayer & Greeno, 1972;Mayer, Stiehl, & Greeno, 1975). One method of capturing students' interest and helping them to gain conceptual understanding in statistics has been to embed problems within interesting cover stories and data sets (Macnaughton, 2002).…”
mentioning
confidence: 99%